2007
DOI: 10.4161/hv.3.5.4459
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Reactogenicity, and Immunogenicity of a Recombinant Protective Antigen Anthrax Vaccine Given to Healthy Adults

Abstract: Background: Bacillus anthracis causes anthrax, a vaccine-preventable zoonotic disease that may follow intentional or unintentional exposure to its spores. Although an anthrax vaccine is currently licensed in the USA, better vaccines are desirable for both pre-and post-exposure prophylaxis.Methods: Healthy adults, aged 18-40 years, received anthrax immunization with either licensed Anthrax Vaccine Adsorbed (AVA, BioThrax™), or an experimental recombinant Protective Antigen vaccine (rPA) produced from an avirule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 21 publications
4
49
0
Order By: Relevance
“…Considering that rPA will most certainly be a constituent of the next-generation anthrax vaccine (9,14,15,15,18), much remains to be done in terms of identifying the specific regions of PA that elicit neutralizing (and non-neutralizing) antibodies, and to better understand how these antibodies interfere (or not) with toxin attachment, oligomerization, and translocation (17,36,45). For example, in our screen to identify domain 4 MAbs, we identified 33 MAbs that reacted with domains 1 or 2.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that rPA will most certainly be a constituent of the next-generation anthrax vaccine (9,14,15,15,18), much remains to be done in terms of identifying the specific regions of PA that elicit neutralizing (and non-neutralizing) antibodies, and to better understand how these antibodies interfere (or not) with toxin attachment, oligomerization, and translocation (17,36,45). For example, in our screen to identify domain 4 MAbs, we identified 33 MAbs that reacted with domains 1 or 2.…”
Section: Discussionmentioning
confidence: 99%
“…As PA is the major protective antigen in the anthrax vaccine adsorbed (AVA, the only U.S.-licensed anthrax vaccine [57]), efforts to develop next-generation anthrax vaccines have been focused on strategies using purified PA (23) (24). In this murine study, we showed that the immunogenicity of PA was enhanced by formulation with Advax adjuvant and to a lesser extent with murabutide and that this translated into enhanced protection against a B. anthracis aerosol challenge compared to mice immunized with PA administered alone.…”
Section: Discussionmentioning
confidence: 99%
“…Although, to date, human trials of PA vaccines have used alum adjuvant (23,24), other adjuvants, including Ribi adjuvant formulation for parenteral formulations (25) and cholera toxin and poly(I·C) for intranasal formulations (26,27), have been shown to be effective in animal studies. Hence, use of alternative adjuvant technologies (28) may allow the development of moreeffective and better-tolerated PA vaccines.…”
mentioning
confidence: 99%
“…Recombinant PA-based vaccines have demonstrated protective properties in several animal models, including rhesus macaques, against B. anthracis subcutaneous (SQ) and aerosol challenges (2)(3)(4). Vaccines based on recombinant PA (rPA) are being considered as novel anthrax vaccine candidates (5,6).…”
mentioning
confidence: 99%